A Concise Review on C-Reactive Protein and their Test - Khobare, Ms. Mayuri (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Interactions in conjunction with the inherent optical properties of quantum dots (QDs) resulted in lower background single increased sensitivity and ability to detect C-reactive protein (CRP) down to 0.79 mg/L with only microliters serum sample in addition the developed assay in simple past and can quantitatively detect CRP with a detection limit up to 200 mg/L clinical test result of our QD-based immune filtration assay, which are well correlated with the traditional latex enhance immune agglutination aggregation.